Current status and potential of biomass utilization in ferrous metallurgical industry. (February 2017) - Wei, Rufei; Zhang, Lingling; Cang, Daqiang; Li, Jiaxin; Li, Xianwei; Xu, Chunbao Charles
Abstract: This paper provides a critical review on the current status and potential of biomass utilization in ferrous metallurgical processes, i.e., the blast furnace (BF) – basic oxygen furnace (BOF) route, the direct reduction (DR) – electric arc furnace (EAF) route, the scrap – EAF route and the other routes. In the BF-BOF route, biomass can be used as a fuel for iron ore sintering, or as a raw material for the production of bio-coke, and utilized for blast furnace injection. In the DR-EAF route, direct reduction iron can be produced form iron ore and biomass pellet. In the scrap – EAF route, biomass can be utilized in EAF through a cogeneration system. In addition, biomass can be utilized in magnetic separation of refractory low-grade iron ore, in reuse of iron and steel slag, or as an adsorbent for pollutant control, etc. The challenges and outlook of biomass utilization in metallurgical industry are also discussed in this paper.